Clinical Linguistics - Cummings, Louise (Edinburgh University Press, 2022)
Louise Cummings provides a comprehensive introduction to speech and language therapy which will give SLT students an excellent starting point for a wide range of communication impairments.The Royal College of Speech and Language Therapists estimates that 2.5 million people in the UK have a communication disorder. Of this number, some 800,000 people have a disorder that is so severe that it is hard for anyone outside their immediate families to understand them. In Clinical Linguistics, Louise Cummings provides a comprehensive introduction to speech and language therapy which will give SLT students an excellent starting point for a wide range of communication impairments. In chapters that are dedicated to the discussion of individual communication disorders, Cummings argues that no treatment of this area can reasonably neglect an examination of the prevalence and causes of communication disorders. The assessment and treatment of these disorders by speech and language therapists are discussed at length. Key FeaturesContains up-to-date research into communication disordersDescribes the various technological innovations that are integral to the work of speech and language therapistsExplores disorders of cognitive development, disorders of speech and language development, acquired communication disorders and disorders of voice